DAMPAK MEDIA SOSIAL DAN INTERNET TERHADAP PERILAKU REMAJA DI ERA DIGITAL - Angela, Yepi (Fakultas Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatullah Jakarta, 2025)
This study investigates how social media and the internet affect teenage behavior in the digital age. This study examines the advantages and disadvantages of social media use for teenagers, particularly in relation to schooling and social contact, using a qualitative methodology based on literature reviews. The study's findings demonstrate how social media promotes learning, grows social networks, and makes information easier to obtain. However, there are drawbacks as well, like the possibility of content abuse, addiction, and a decline in in-person social engagement. In order to reduce social media's detrimental effects and optimize its positive effects on teenage development, this study highlights the significance of digital literacy instruction, parental monitoring, and educational institution assistance. Adolescents' social, emotional, and academic growth can be supported by social media if used responsibly.